The Effect Of The Problem Based Learning Model On The Ability Of Front Roll Floor Gymnastics Movement - Roni Romansah; Ramdhani Rahman (Jurnal Pendidikan Jasmani (JPJ), 2026)
The purpose of this study was to determine the improvement of students' movement abilities in the front roll floor gymnastics material at MAN 1 Kuningan. The research method used was a quantitative method, with a One Group Pretest Posttest design. This study involved 24 students of class XI MAN 1 Kuningan. Data collection was carried out through observation, interviews, documentation and practical tests. The results of the study showed that the Problem Based Learning model was declared effective and could improve the front roll floor gymnastics movement ability. The level of effectiveness was proven by the n-gain test which was quite effective. This indicates that the Problem Based Learning model was declared feasible and effective in improving the front roll floor gymnastics movement ability..